A Rare Anomaly in Circle of Willis - Pokhrel, Rishi; Bhatnagar, Rajan (Medical Journal of Shree Birendra Hospital, 2013)
Anomalies in circle of Willis are very common and complete functioning ring as classically described is found only in 85 % of population. Most anomalies however are in posterior segment. We report a case of rare anomaly of anterior segment, where anterior communicating artery was completely absent and both anterior cerebral arteries arose from right internal carotid artery. Since both the frontal lobes of cerebrum are dependent upon right internal carotid artery for vascularization, with a poor communication with its left counterpart, ischemia or stroke in an event of pathological or iatrogenic compression of right internal carotid artery can occur.Medical Journal of Shree Birendra Hospital; January-June 2013/vol.12/Issue1/41-42DOI: http://dx.doi.org/10.3126/mjsbh.v12i1.9093